2010
DOI: 10.1021/ml100077x
|View full text |Cite
|
Sign up to set email alerts
|

Novel 3-Oxazolidinedione-6-aryl-pyridinones as Potent, Selective, and Orally Active EP3 Receptor Antagonists

Abstract: High-throughput screening and subsequent optimization led to the discovery of novel 3-oxazolidinedione-6-aryl-pyridinones exemplified by compound 2 as potent and selective EP 3 antagonists with excellent pharmacokinetic properties. Compound 2 was orally active and showed robust in vivo activities in overactive bladder models. To address potential bioactivation liabilities of compound 2, further optimization resulted in compounds 9 and 10, which maintained excellent potency, selectivity, and pharmacokinetic pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 22 publications
(37 reference statements)
0
14
0
Order By: Relevance
“…3 Arylpyrimidinone substructures have also been featured in some of our FGFR1 kinase inhibitors. 2 Furthermore, 6-aryl-pyridinones have been reported as orally active inhibitors of the EP3 receptor, 30 and as core structures of different non-peptidic inhibitors of human leukocyte elastase 31 and interleukin-1β converting enzyme. 32 Thus, ten 6-aryl-pyridinones were also selected for parameterization ( 21 – 30 in Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…3 Arylpyrimidinone substructures have also been featured in some of our FGFR1 kinase inhibitors. 2 Furthermore, 6-aryl-pyridinones have been reported as orally active inhibitors of the EP3 receptor, 30 and as core structures of different non-peptidic inhibitors of human leukocyte elastase 31 and interleukin-1β converting enzyme. 32 Thus, ten 6-aryl-pyridinones were also selected for parameterization ( 21 – 30 in Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…Prostaglandin EP 3 receptor ( Chen and Kuo 2019 ) could regulate the excitability of bladder smooth muscle and is considered a potential target for OAB. Jin et al (2010) reported a series of 3-oxazolidinedione-6-aryl-pyridinones ( 102 ) as selective EP 3 receptor antagonists, generated by the optimization of 100 and 101 which were identified through the high-throughput screening (HTS) method. A thorough investigation on 101 indicated the lead compound exhibited excellent pharmacokinetic profiles and robust potency in several overactive bladder models ( Figure 15 ).…”
Section: Ep 3 Receptor Antagonistsmentioning
confidence: 99%
“… EP 3 inhibitory activities of 3-oxazolidinedione-6-aryl-pyridinones ( Jin et al, 2010 ). a Value of functional p K i(fp K i) was obtained from a EP 3 fluorometric imaging plate reader (FLIPR) assay.…”
Section: Ep 3 Receptor Antagonistsmentioning
confidence: 99%
“…Adapting the procedure of Jin et al 34 To a cooled (0 °C) suspension of NaH (310 mg, 7.75 mmol) in DMF (15 mL) was added naphthol 16 (1.00 g, 6.28 mmol) portionwise. The reaction mixture was warmed to RT over 15 min then cooled to 0 °C.…”
Section: -Methoxynaphthalen-1-amine (23)mentioning
confidence: 99%